A high energy density 3D nano-carbon based magnesium hydroxide reversible chemical reaction heat storage material synthesis and heat transfer performance investigation. (June 2022) - Li, Shijie; Yang, Xiangyu; Li, Xinyu; Qu, Wenshan; Zhou, Tao; Dong, Ti; Deng, Lisheng; Zhang, Jin; Zhao, Jianguo
Highlights: Mg(OH)2 based high temperature TCMs modified by 3D-graphene nanocarbons. The designed 3D-Graphene/Mg(OH)2 composites have excellent heat storage density. Heat transfer numerical simulation of 3D-Graphene/Mg(OH)2 composites was applied. Abstract: Magnesium hydroxide composite chemical heat storage materials were constructed with in-situ prepared 3D-Graphene. Mg(OH)2 particles were anchored onto the surface of the nanosupport by deposition-precipitation method. According to the heat transfer numerical simulation, addition of 3D-Graphene could greatly change the temperature distribution in the reactor and was easier to export thermal energy to the outside thermal load side. This energy storage system could output thermal energy at around 200 °C and absorbed heat at the range of 300–400 °C. Transmission electron microscopy result indicated that the particle size of Mg(OH)2 was primarily in the range of 20–50 nm. X-ray diffraction characterization showed that the magnesium hydroxide was well dispersed in the composite material. This material provided an obviously enhanced heat storage density (610 kJ/kg), no distinct attenuation and greatly improved hydration rate compared with those of magnesium oxide because of hydrogen bonding effect in composite materials. 3D-Graphene lead to obvious decomposition activation energy decreasing of Mg(OH)2 that would improve its utilization in the heat storage process. This was probably due to its surface effect. 3D-Graphene/Mg(OH)2 -1 showed the lowest activation energy (116.7 kJ/mol), The thermal conductivity of the composite material was 9.4 times higher than that of Mg(OH)2 as a result of the addition of 3D-Graphene. The proposed method provided a facile and valid technique for thermal energy utilization and the synthesis of nano-composed materials with enhanced chemical heat storage performance. Graphical abstract: Image, graphical abstract